Accessibility and visibility of genetic testing for haemophilia across Europe: Where do we stand?. Issue 1 (12th October 2022) - Lannoy, Nathalie; Hermans, Cedric
Abstract: Introduction: Haemophilia is characterized by bleeding complications resulting from clotting factor VIII (FVIII) or IX (FIX) deficiency. Identifying the causal pathogenic genetic variant denotes a vital aspect of haemophilia management. Aim: This study evaluated the accessibility and performances of genetic testing for haemophilia across Europe. The types of genetic analyses, techniques used, turn‐around time (TAT) and costs were collected and analysed, as were data updating and quality control. Methods: Reported data were retrieved from open access resources, including international databases, Google, laboratory websites, PubMed and government organizations. Results: Overall, 51 genetic laboratories across 15 European countries providing recently updated molecular haemophilia testing were identified. Gene sequencing for small variants of both F8 and F9 genes was provided in most surveyed laboratories. Almost two‐thirds of them offer analysis for inversions using a polymerase chain reaction (PCR) method and detection of copy number variation (CNV) using multiplex ligation‐dependent probe amplification (MLPA). Cost and TAT were found to vary considerably. In total, 74% of laboratories exhibited a last modified date or change history. The same percentage of laboratories was in possession of an ISO 15189 standard accreditation, whereas only few of them recently performed external quality assessment schemes (EQA) for haemophilia. Conclusion: Despite several initiatives to improve access to genetic testing for haemophilia, such access must still be improved. Our study similarly revealed the large heterogeneity of the variants tested, techniques employed, TAT, cost and quality among the surveyed laboratories.